Komunikasi Dakwah Walisongo Sebagai Strategi Dakwah Di Nusantara - Estuningtiyas, Retna Dwi (The International Journal of Pegon : Islam Nusantara civilization, 2023)
Islam developed in the archipelago around the 13th century AD with Walisongo's services in spreading Islamic teachings. In Javanese society, the term walisongo is a name that is very well known and has a special meaning and is used to refer to the names of these figures, which are seen as the beginning of Islamic broadcasting in Java. Qualitative research with a literature study approach is expected to be able to find out about da'wah communication as a da'wah method used by Walisongo in preaching Islam. The application of a flexible or good da'wah method with a cultural or acculturation approach is carried out well so that it can be well received by the Javanese community and that walisongo is not considered a threat on the island of Java. Islam berkembang di Nusantara sekitar abad 13 M dengan jasa Walisongo dalam penyebaran ajaran Islam. Dalam masyarakat Jawa, sebutan Walisongo adalah nama yang sangat terkenal dan memiliki arti khusus, yang digunakan untuk merujuk nama-nama tokoh tersebut dipandang sebagai awal mula penyiaran Islam di Jawa.Penyebaran dengan pemilihan wilayah dakwah tentu mempunyai pertimbangan tersendiri. Penelitian kualitatif dengan pendekatan studi pustaka ini diharapkan dapat mengetahui komunikasi dakwah debagai metode dakwah yang dipergunakan Walisongo dalam mendakwahkan Islam. Penerapan metode dakwah yang lentur atau baik dengan pendekatan budaya atau akulturasi dilakukan dengan baik sehingga dapat diterima baik oleh masyarakat Jawa, sehingga walisongo tidak dianggap sebagai ancaman di Pulau Jawa.